2023
DOI: 10.1186/s12912-023-01208-w
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ reflections on caring for sexual and gender minorities pre-post stigma reduction training in Uganda

Abstract: Background Men who have sex with men (MSM) and transgender women (TGW) have a significant HIV burden worldwide. Data from eight countries across sub-Saharan Africa found a pooled HIV prevalence of 14% among MSM and 25% among TGW. Stigma and discrimination among healthcare providers are barriers to healthcare access by these populations. We sought to explore nurses’ attitudes before and after sensitivity training to reduce stigma in HIV prevention and care provision to MSM and transgender person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Therefore, it is necessary to take measures to strengthen identity recognition and reduce HIV-stigma, thereby reducing the prevalence of suicidal ideation among HIV-positive MSM. A qualitative study conducted in Uganda showed that increasing knowledge of specific care concerning MSM among healthcare providers in general healthcare settings to mitigate negative experiences of MSM is helpful to identity recognition [ 42 ]. Another cross-sectional survey conducted in Changsha pointed out that increasing awareness of mental health conditions and strengthening self-regulation skills are useful to avoid HIV-related stigma and further reduce suicidal ideation among HIV-positive MSM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to take measures to strengthen identity recognition and reduce HIV-stigma, thereby reducing the prevalence of suicidal ideation among HIV-positive MSM. A qualitative study conducted in Uganda showed that increasing knowledge of specific care concerning MSM among healthcare providers in general healthcare settings to mitigate negative experiences of MSM is helpful to identity recognition [ 42 ]. Another cross-sectional survey conducted in Changsha pointed out that increasing awareness of mental health conditions and strengthening self-regulation skills are useful to avoid HIV-related stigma and further reduce suicidal ideation among HIV-positive MSM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Criminalization and oppressive legislature were discussed in five studies [ 29 , 48 , 68 70 ]. Findings revealed that criminalization directly and indirectly affects healthcare service access.…”
Section: Resultsmentioning
confidence: 99%
“…Some TGD people may delay seeking care and treatment, while others may face barriers like community discrimination that prevent them from reaching health facilities [ 68 ]. Several nurses in a study by Muwanguzi et al [ 48 ] expressed reluctance, fearing criminal complicity, and mentioned their inclination to involve the police when encountering TGD people.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that sexual minorities experience stigma and discrimination worldwide (23)(24)(25). In Brazil, the underestimation of MSM and WSW size estimates based on the self-declared sexual orientation suggests that gay and bisexual communities experience various psychological challenges related to their sexuality and gender identity disclosure (26).…”
Section: Discussionmentioning
confidence: 99%